Mental practice promotes motor anticipation: evidence from skilled music performance - Bernardi, Nicolò F.; De Buglio, Matteo; Trimarchi, Pietro D.; Chielli, Alfonso; Bricolo, Emanuela (Frontiers in Human Neuroscience, 2013)
Mental practice (MP) has been shown to improve movement accuracy and velocity, but it is not known whether MP can also optimize movement timing. We addressed this question by studying two groups of expert pianists who performed challenging music sequences after either MP or physical practice (PP). Performance and motion-capture data were collected along with responses to imagery questionnaires. The results showed that MP produced performance improvements, although to a lower degree than PP did. MP and PP induced changes in both movement velocity and movement timing, promoting the emergence of movement anticipatory patterns. Furthermore, motor imagery was associated with greater changes in movement velocity, while auditory imagery was associated with greater movement anticipation. Data from a control group that was not allowed to practice confirmed that the changes in accuracy and kinematics were not due to mere repetition of the sequence during testing. This study provides the first evidence of an anticipatory control following MP and extends the present knowledge on the effectiveness of mental practice to a task of unparalleled motor complexity. The practical implications of MP in the motor domain are discussed.